Organocatalytic enantioselective Diels–Alder reaction between hydroxymaleimides and in situ generated nitrosoalkenes for direct preparation of chiral hemiketals with 1, 2-oxazine skeleton. Issue 22 (15th September 2021) - Xiang, Min; Li, Chen-Yi; Zhang, Jian; Zou, Ying; Li, Wen-Sheng; Tian, Fang; Wan, Wen-Juan; Wang, Li-Xin
Abstract : Organocatalytic Enantioselective IEDDA reaction between hydroxymaleimides and in situ generated nitrosoalkenes has been disclosed, a series of chiral hemiketals containing 5, 6-dihydro-4 H -l, 2-oxazines and succinimide frameworks have been prepared. Abstract : An organocatalyst promoted enantioselective inverse-electron-demand oxa-Diels–Alder (IEDDA) reaction between hydroxymaleimides and in situ generated nitrosoalkenes has been revealed, and a wide range of chiral hemiketals containing 5, 6-dihydro-4 H -1, 2-oxazines and succinimide frameworks with two adjacent quaternary stereogenic centers have been effectively prepared for the first time with excellent results (up to 99% yield, up to 99 : 1 dr, up to >99% ee) even at a scale-up preparation under mild conditions.